Analisis Kinerja Perusahaan Sebelum dan Saat Pandemi serta Pengaruhnya terhadap Nilai Perusahaan - Benarivo, Hiras; Masripah, Masripah (Universitas Prasetiya Mulya, 2023)
This study aims to conduct tests and analyses related to differences in financial performance before and after the COVID-19 pandemic and to see whether financial performance affected the value of food and beverage companies listed on the Indonesia Stock Exchange in 2018-2021. This research proxies firm value using price-to-book value (PBV). Meanwhile, financial performance is divided into three independent variables: Return on Assets as a measure of profitability, receivable turnover, and debt-to-equity ratio (DER) as a measure of leverage. This quantitative research method uses purposive sampling so that 23 companies are obtained, 46 samples for the different tests, and 92 samples for the influence test. This research used the paired sample t-test and the Wilcoxon test for the difference test, and the panel data regression test was used for the effect test. Processing data is carried out using the STATA Version 16 application. Based on the results of the tests that have been carried out, it is found that profitability differs between before and during the COVID-19 pandemic. In contrast, receivable turnover and leverage have no difference. Lastly, the influence test in this study shows that profitability significantly affects firm value, while accounts receivable turnover and leverage do not affect the firm value.